Management of Musculoskeletal Manifestations in Inflammatory Bowel Disease - Tejas Sheth; C. S. Pitchumoni; Kiron M. Das (Gastroenterology Research and Practice)
Musculoskeletal manifestations are the most common extraintestinal manifestations in inflammatory bowel diseases. Some appendicular manifestations are independent of gut inflammation and are treated with standard anti-inflammatory strategies. On the other hand, axial involvement is linked to gut inflammatory activity; hence, there is a considerable amount of treatment overlap. Biological therapies have revolutionized management of inflammatory bowel diseases as well as of associated articular manifestations. Newer mechanisms driving gut associated arthropathy have surfaced in the past decade and have enhanced our interests in novel treatment targets. Introduction of biosimilar molecules is expected in the US market in the near future and will provide an opportunity for considerable cost savings on healthcare. A multidisciplinary approach involving a gastroenterologist, rheumatologist, and physical therapist is ideal for these patients.